PELATIHAN PENATAUSAHAAN POS TIKET KAWASAN WISATA ALAM SEMBALUN - Karim, Nina Karina; Atikah, Siti; Lenap, Indria Puspitasari (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
Sembalun tourism area has become one of the leading tourism destination in Lombok island. Since the launch of Sembalun7Summits program, the number of tourist coming to Sembalun to experience the sensation of venturing through the beautiful landscapes has increased significantly. This has opened a wide opportunity for this agricultural village to increase its income from tourism. This activity aimed to provide the knowledge for guards of entry posts to hiking trails to help them manage and record visitor data so that they can keep track of entry charges collected from visitors. Better records of entry charges and visitors will enable the guards to manage the income they have generated in order to map the expenses needed to provide better service for visitors. These services include safety measures for visitors and improved income for not only the guards in the entry posts but also villagers in surrounding areas. The training was participated by 25 post guards from ten hiking posts and five members of the Sembalun Foundation organization which is the partner of this community development activity. After the training, the post guards made an agreement to start using the Google Form designed by our team to be used as a means to record visitor data. This form will be provided in each hiking post’s social media account where visitors can schedule and register their hiking trip.